ISOLATION AND CLONING OF ENV-TM SUBUNIT GENE OF JEMBRANA DISEASE VIRUS IN THE PROKARYOTIC EXPRESSION VECTOR pGEX-2T - Asmarani Kusumawati; Ronny Martien; Soesanto Mangkoewidjojo; Joeannes Sri Widada (Jurnal Sain Veteriner, 2003)
.